2014
DOI: 10.1097/won.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

Living With a Long-term, Indwelling Urinary Catheter

Abstract: Catheter users' experiences of living with a catheter are shaped by a variety of interrelated factors. Some participants were determined to overcome catheter-related problems and develop self-reliance while others adopted a more resigned approach to living with a catheter. Having a catheter enabled some participants to experience greater freedom while others led more restricted lives as a consequence of catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 14 publications
1
50
0
1
Order By: Relevance
“…Specific adjustments were identified during this period, including allowing extra time in the day for bladder management, changing the types of clothing to help hide the bag, modifying sleep habits (eg, protecting the mattress from unexpected indwelling catheter‐drainage bag disconnections, having an emergency trouble‐shooting kit for night‐time problems, and keeping the bag from pulling when they roll over) and discovering the challenges associated with travel and social activities. A problem‐solving mentality made this adjustment process easier . As part of the normalization process, participants described how an indwelling catheter became a part of them, and faded into the background to be ignored; the person became aware of it as an object when it did not work properly, or if it led to embarrassment or shame .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific adjustments were identified during this period, including allowing extra time in the day for bladder management, changing the types of clothing to help hide the bag, modifying sleep habits (eg, protecting the mattress from unexpected indwelling catheter‐drainage bag disconnections, having an emergency trouble‐shooting kit for night‐time problems, and keeping the bag from pulling when they roll over) and discovering the challenges associated with travel and social activities. A problem‐solving mentality made this adjustment process easier . As part of the normalization process, participants described how an indwelling catheter became a part of them, and faded into the background to be ignored; the person became aware of it as an object when it did not work properly, or if it led to embarrassment or shame .…”
Section: Resultsmentioning
confidence: 99%
“…Problems include medical complications, problems arising from the catheter design, or an increase in the frequency of urinary infections; they are generally considered either an intermittent nuisance, or a defining aspect of bladder function. The importance of these complications may not be evident to healthcare workers; for example, one participant stated that “I wouldn't care if the house burnt down, but if that bloody [indwelling] catheter blocks up I am in real trouble.” The unpredictability of catheters was a frequent concern, and contributes to anxiety and rituals (such as frequently patting the leg bag of an indwelling catheter through clothing) . Not surprisingly, travel and social activities are redefined within the context of catheter management.…”
Section: Resultsmentioning
confidence: 99%
“…While some persons might have received instruction about drinking a lot of fluids, such as those with spinal cord injuries who often learn this in rehabilitation (Fowler, Godfrey, Fader, Timoney, & Long, 2014), others may not have had much instruction. In one of our previous studies, catheter users said they knew they were to drink extra fluids, but they did not know how much to drink, nor were they given guidance on making behavior changes (Wilde & Dougherty, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A catheter valve gives the patient the option of having no collection bag; which avoids the bulkiness and visibility of tubing and bags 18. Laboratory studies have additionally shown that valve use can increase time to catheter blockage,38 but clinical evidence is lacking and the devices are not suitable for all patients (box 4).…”
Section: Which Catheter and Drainage Solution To Choosementioning
confidence: 99%